Perspectives on priests' cultic and pedagogical malpractices in Malachi 1:6-2-9 and their consequent acts of negligence - Boloje, Blessing Onoriode (Journal for semitics, 2013)
This article presents some perspectives on the priestly class in the book of Malachi with respect to their attitude toward the cult, their pedagogical responsibility and their consequent acts of negligence. It demonstrates that the priests in Malachi's day despised their covenantal relationship with Yahweh by disrespecting, dishonoring, despising and defiling Yahweh, and they questioned his accusations as if he either lied or was ignorant. Priests were saddled with the responsibility of guarding the entire cultic life of the people. Thus, the principal way they despised and defiled Yahweh day after day was through deficient and unacceptable offerings (1:6-2:3). On the other hand, the teaching aspect is considered to have been an integral part of the priestly office. The priests in Malachi are accused of causing many to falter by their pedagogical functions and or obligations to Yahweh (2:8) and by implication, the people of Yahweh were led astray for lack of the knowledge of God. Their failure was indeed the ground for the humiliating judgement pronounced on them by Yahweh in the inspired words of Malachi 1:6-2:9. These perspectives offer Yahweh's people and also contemporary religious leaders within the Christian tradition a glimpse into the nature and demands of the priesthood - that which requires men of profound moral character both because they are messengers of God who make known divine commands to the faithful, and because they have the privilege to offer sacrifices.